DESAIN SISTEM INFORMASI SEKOLAH BERBASIS ANDROID - Renita Fitriani; Muhammad Tajuddin (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2016)
Information technology today has grown rapidly, not least in Indonesia. almost all large and medium enterprises to apply information technology to help oprasi business. The use of this technology covers virtually all ages, ranging from young children to adults especially Smart phone. Smart phone is a phone with capabilities beyond computing and connectivity. Smat phone an Android-based smart phone that dominate the world's smart phone market, making the Android-based applications easier when compared to other operating systems. Likewise, the implementation of education, especially Senior High School (SMA). SMAN XXX require the system to help the school and students that there SMAN XXX. Where the application is built with the programming language PHP (Personal Home Page), Database MySQL, XAMPP, Web Server and its utlity software using android studio. System development methodology that I use is the Waterfall methodology. This system generates data information teacher, student data, employee data, and the data on tuition payments. This application is also in lengakapi with features share the announcement, in which not only the admin can share information or send information, but students, teachers, and employees can also send or transmit information through features share the announcement, which will be received the user a notification announcement, extracurricular and SPP notifications and other announcements.